Determining role of thymus in immune pathogenesis of autoimmune, oncological and infectious diseases - V. A. Kozlov (Медицинская иммунология, 2023)
Research data presented in the article are based, mainly, on the concept that thymus, together with bone marrow represent the central organ of immune system being the source of all T cell populations that, following their migration from thymus to periphery, participate in development of immune response to any antigens of viral, bacterial and tissue origin, and to any allergens. This difference is principal, as opposed to the bone marrow which produces other members of immune response, i.e., dendritic cells, macrophages, B cells. E.g., the bone marrow also generates the cells which migrate to thymus where they undergo differentiation to the T cells. Over last 50 years, a plethora of data was accumulated on the leading role of immune system  in pathogenesis of virtually all socially significant human diseases affecting the modern mankind, including infectious and malignant disorders, atherosclerosis, autoimmune and allergic diseases. Moreover, current studies show that the aberrant functions of different T cell populations play the leading role in pathogenesis of these diseases. These T cell disturbances in peripheral areas of different organs are proven to develop, mainly in the thymic area. Hence, thymus is a producing organ of T cells with altered functional activities which promote pathogenetic changes in these disorders. Currently, the entire set of immunotherapeutic approaches is aimed for correction of disturbances among the same T cells subpopulations at periphery, without taking into account thymic mechanisms which have induced these disturbances before their emigration from thymus. One should, therefore, develop novel methods and approaches to correct these alterations within thymic area.